A valuation framework for assessing compensation arising from oil spills in the Niger delta area of Nigeria / Gabriel Kayode Babawale and Titilayo Ukabam - Babawale, Gabriel Kayode; Ukabam, Titilayo (Faculty of Architecture, Planning and Surveying, 2019)
Both empirical and anecdotal evidences suggest that valuers in the study area do not generally follow appropriate valuation procedure particularly when assessing compensation for environmental pollution arising from oil spills. This abuse of the valuation process, according to a number of extant studies, is largely responsible for widespread incoherent, inconsistent and controversial compensation assessment with its numerous potential socio-economic repercussions for a nation that oil revenue is her economic mainstay. This study is based exclusively on secondary data drawn from results of extant studies, valuation reports, relevant statutes and civil laws including several years of experience of one of the authors as expert witnesses in cases relating to compensation for oil spills in the study area. The paper is particularly written in response to Babawale (2013) which observed certain fundamental procedural deficiencies in valuation for compensation with "potentially grave repercussion for the integrity and the future of the valuation profession in the study area." To redress the observed deficiencies and save the profession from further embarrassment, the study provides practitioners with an institutional perspective; a purpose-designed procedural framework that reflects and addresses the peculiarities of valuation for compensation for oil spills. Besides contributing to the recurrent debate on the vexed subject of compensation for oil spills and filling up part of the apparent wide gap presently existing in the body of knowledge particularly in Nigeria, the eight-step valuation process proffered is expected to boost valuers' confidence and improve the reliability of valuation for compensation in the study area. The ultimate goal is overall improvement in the practice of valuation for compensation in the study area in particular, and Nigeria as a whole. This is expected to minimize the costs of protracted court cases including the contention and restiveness that is often associated with compensation matters in the study area.